Allosteric regulation of UBIAD1 trafficking from ER to Golgi revealed by chemical genetic screening - Dong-Jae Jun; Marc M. Schumacher; Youngah Jo; Rebecca A. Faulkner; Yangyang Yang; Jet Tsien; Tian Qin; Russell A. DeBose-Boyd (Proceedings of the National Academy of Sciences, 2025)
Schnyder corneal dystrophy (SCD) is a rare autosomal dominant condition characterized by the opacification of the cornea owing to the abnormal deposition of cholesterol. SCD-associated mutations have been identified in the gene encoding UbiA prenyltransferase domain-containing protein-1 (UBIAD1), which uses geranylgeranyl pyrophosphate (GGpp) to synthesize the vitamin K 2 subtype menaquinone-4 (MK-4). Beyond its enzymatic role, UBIAD1 serves as a key regulator of the endoplasmic reticulum (ER)-localized enzyme 3-hydroxy-3-methylglutaryl coenzyme A reductase (HMGCR), the rate-limiting enzyme in the mevalonate pathway that produces cholesterol and nonsterol isoprenoids such as GGpp and MK-4. Sterol-induced binding to UBIAD1 inhibits the sterol-accelerated ER-associated degradation (ERAD) of HMGCR to maintain the synthesis of nonsterol isoprenoids under conditions of cholesterol repletion. GGpp dissociates the HMGCR–UBIAD1 complex, triggering maximal ERAD of HMGCR and ER-to-Golgi translocation of UBIAD1. However, SCD-associated UBIAD1 resists this GGpp-induced dissociation and remains sequestered in the ER. ER retention of UBIAD1 leads to inhibition of HMGCR ERAD, promoting increased synthesis and accumulation of cholesterol. Here, chemical genetic screening was utilized to identify molecules that restored Golgi localization of SCD-associated UBIAD1 (N102S) and thereby relieve inhibition of HMGCR ERAD. We found that the chemotherapeutic tyrosine kinase inhibitor Apatinib stimulated ER-to-Golgi transport of both N102S and wild type UBIAD1. This effect required GGpp but was independent of Apatinib’s tyrosine kinase inhibition. Apatinib-mediated Golgi transport of UBIAD1 enhanced the ERAD of HMGCR. Photoaffinity labeling studies indicated that Apatinib binds directly to UBIAD1, suggesting that the drug allosterically activates GGpp-induced transport of UBIAD1 from the ER to the Golgi.